KEY FACTORS INFLUENCING GENERATION Z CONSUMER SATISFACTION AND PURCHASE DECISION FOR LOCAL MOISTURIZERS - Winnie Irene (Ikatan Dosen Menulis, 2024)
The Indonesian skincare market, valued at USD 586.4 million and projected to reach USD 2.8 billion by 2028, has grown rapidly, especially among Generation Z, who prioritize product quality, affordability, and effectiveness. This study examines the key factors influencing consumer satisfaction and purchase decisions for local moisturizers among Generation Z in Indonesia. Using a quantitative approach, data was collected from 2,045 respondents aged 12-27 who have tried local moisturizer products through online surveys on Instagram and TikTok. Data analysis used PLS-SEM, focusing on the impact of product quality, price, promotion, and brand image on consumer satisfaction and purchase decisions. The results indicate that product quality and brand image are the main factors influencing consumer satisfaction, which in turn affects purchase decisions. Although competitive pricing and effective promotions also contribute, they are secondary. These findings provide insights for local skincare brands to enhance market strategies, meet the needs and preferences of Generation Z, and drive sustainable growth. By understanding these dynamics, local brands can enhance customer loyalty, encourage repeat purchases, and foster word-of-mouth promotion in the competitive skincare industry. This research emphasizes the importance of aligning product offerings with consumer expectations and leveraging brand reputation to gain a competitive edge.